Analisis Keamanan Fisik Data Prodi Sistem Informasi UIN Sumatera Utara Medan Menggunakan Standar ISO 27001 - Harun Yahya; Mahzura Aznur; Nadila Agnestesia; Ali Ikhwan (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
Physical security is the first step in computer security. If physical storage is not properly secured, data, even the computer applications themselves, cannot be guaranteed to be secure. Analysis of Physical Data Security of the Information Systems Study Program UIN North Sumatra Medan using point A.9 of the ISO 27001 Standard. Analysis of the physical security of the information system study program data was carried out through literature review, use of ISO 27001 points, interviews with related parties regarding the physical security of the current study program data. This study aims to find out the details and problems faced by the Medan North Sumatra UIN Information Systems Study Program in using its physical security system.